Determinants of treatment-seeking behaviour and healthcare provider choice in Afghanistan in 2018: a cross-sectional study - Sandra Alba; Egbert Sondorp; Konrad T Juszkiewicz; Sayed Ataullah Saeedzai; Margo van Gurp; Sayed Rahim Arab; Sohrab Safi; Mohammad Haris Abdianwall (BMJ Public Health)
Introduction In Afghanistan, remarkable achievements have been made in improving access to healthcare and health outcomes since the introduction of essential healthcare packages. Nonetheless, sociodemographic and geographical inequities persist, and out-of-pocket expenditures are high. This study investigates the client and provider determinants of access to care that affect treatment-seeking behaviour in 2018.Methods Secondary data analysis using data on treatment-seeking behaviour in public and private healthcare from the Afghanistan Health Survey 2018 was combined with data on the quality of public healthcare facilities from a national healthcare facility assessment of the same year. Logistic regression analyses were performed to explore associations between client characteristics and accessibility of public healthcare facilities, and treatment-seeking behaviour and choice of public versus private healthcare provider.Results The results suggest that the odds of seeking treatment are lowest among the rural poor. The odds of treatment-seeking and choosing a public healthcare provider are higher for pregnancy-related health needs but lower for chronic conditions. Affordability of healthcare was associated with lower odds of treatment-seeking (OR 0.96, 95% CI 0.95 to 0.98) and using private healthcare providers (OR 0.97, 95% CI 0.96 to 0.99). Increased satisfaction with opening hours (OR 1.04, 95% CI 1.02 to 1.05) and availability of a female nurse or doctor (OR 1.03, 95% CI 1.01 to 1.04) in public health facilities, and a higher level of trust in healthcare provider (OR 1.04, 95% CI 1.03 to 1.06) were associated with higher odds of using public healthcare.Conclusion Afghanistan’s public healthcare system is vital in providing care to the economically disadvantaged and managing infectious diseases and maternal health problems. The private sector plays a dominant role, particularly for those illnesses not covered under the essential healthcare packages. The study suggests opportunities for the public healthcare system to alleviate financial barriers to healthcare access and broaden its service offerings to encompass the management of chronic illnesses.